The influence of E-WOM, brand image, and brand trust on purchasing decisions of skintific skincare products in Batam city - Jevin Ronald; Muhammad Haldy (Trigin Publisher, 2026)
This study examines the influence of Electronic Word of Mouth (E-WOM), Brand Image, and Brand Trust on purchasing decisions for Skintific skincare products in Batam City. The research employed a quantitative approach using questionnaire data collected from 150 respondents who had purchased and used Skintific products. Data analysis was conducted using SPSS version 26, including validity, reliability, classical assumption, multiple linear regression, coefficient of determination, and hypothesis testing. The findings revealed that E-WOM, Brand Image, and Brand Trust each had a positive and significant effect on purchasing decisions. Simultaneously, these variables also significantly influenced purchasing decisions, with the coefficient of determination indicating that 85.6% of purchasing decision variation could be explained by the three independent variables. The results demonstrate that positive digital reviews, strong brand perception, and consumer trust play essential roles in encouraging consumer purchasing behavior toward Skintific skincare products. These findings highlight the importance of maintaining product quality, strengthening brand reputation, and optimizing digital consumer engagement to improve purchasing decisions in the competitive skincare industry.